Heat-Induced Interaction of Milk Proteins: Impact on Yoghurt Structure - Md Asaduzzaman; Md Sultan Mahomud; Mohammod Enamul Haque (International Journal of Food Science)
Heating milk for yoghurt preparation has a significant effect on the structural properties of yoghurt. Milk heated at elevated temperature causes denaturation of whey protein, aggregation, and some case gelation. It is important to understand the mechanism involved in each state of stabilization for tailoring the final product. We review the formation of these complexes and their consequence on the physical, rheological, and microstructural properties of acid milk gels. To investigate the interactions between denatured whey protein and casein, the formation of covalent and noncovalent bonds, localization of the complexes, and their impact on ultimate gelation and final yoghurt texture are reviewed. The information regarding this fundamental mechanism will be beneficial to develop uniform quality yoghurt texture and potential interest of future research.